Regulation of the Ras-Related Signaling Pathway by Small Molecules Containing an Indole Core Scaffold: A Potential Antitumor Therapy - Chen, Fei-Yu; Li, Xiang; Zhu, Hong-Ping; Huang, Wei (Frontiers in Pharmacology, 2020)
The Ras-Related signaling pathway plays an important role in cell development and differentiation. A growing body of evidence collected in recent years has shown that the aberrant activation of Ras is associated with tumor-related processes. Several studies have indicated that indole and its derivatives can target regulatory factors and interfere with or even block the aberrant Ras-Related pathway to treat or improve malignant tumors. In this review, we summarize the roles of indole and its derivatives in the isoprenylcysteine carboxyl methyltransferase-participant Ras membrane localization signaling pathway and Ras-GTP/Raf/MAPK signaling pathway through their regulatory mechanisms. Moreover, we briefly discuss the current treatment strategies that target these pathways. Our review will help guide the further study of the application of Ras-Related signaling pathway inhibitors.